2015
DOI: 10.1517/14656566.2015.1052743
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic treatment options for advanced epithelial skin cancer

Abstract: Vismodegib, a Hedgehog (Hh) inhibitor, was recently approved for the treatment of advanced BCC showing a good efficacy rate and a relatively well-tolerated safety profile in clinical studies. In addition, a number of hedgehog inhibitors are now in Phase I and II trials of advanced BCC demonstrating encouraging results. Phase II studies with epithelial growth factor receptor inhibitors, such as cetuximab, gefitinib, panitimumab and erlotinib have been conducted in patients with advanced SCCs, used either as mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 96 publications
(128 reference statements)
0
22
0
Order By: Relevance
“…Some chemotherapeutic agents have been used to treat SCC such as cisplatin, doxorubicin, 5-fluorouracil, vincristine and bleomycin. Unfortunately, these drugs target all cells with high proliferation rate in the body like bone marrow and hair follicles and cause many significant side effects (5). Other drugs have been demonstrated to have anti-proliferative properties in cancer cells in addition to their conventional therapeutic effects including some antibiotics like doxycycline and ciprofloxacin, some herbal extracts and non-steroidal anti-inflammatory drugs (NSAIDs) (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Some chemotherapeutic agents have been used to treat SCC such as cisplatin, doxorubicin, 5-fluorouracil, vincristine and bleomycin. Unfortunately, these drugs target all cells with high proliferation rate in the body like bone marrow and hair follicles and cause many significant side effects (5). Other drugs have been demonstrated to have anti-proliferative properties in cancer cells in addition to their conventional therapeutic effects including some antibiotics like doxycycline and ciprofloxacin, some herbal extracts and non-steroidal anti-inflammatory drugs (NSAIDs) (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…These treatments have provided acceptable results and present an excellent option for patients with inoperable tumors (Soura, Chasapi, & Stratigos, 2015). These treatments have provided acceptable results and present an excellent option for patients with inoperable tumors (Soura, Chasapi, & Stratigos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These treatments have provided acceptable results and present an excellent option for patients with inoperable tumors (Soura, Chasapi, & Stratigos, 2015). In addition, a number of patients may experience loss of efficacy and tumor recurrence after initial response (Soura et al, 2015). In addition, a number of patients may experience loss of efficacy and tumor recurrence after initial response (Soura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Basal cell carcinoma (BCC) is considered as the most common skin malignancy in patients with fair skin. BCCs are usually associated with a good prognosis and a low metastatic potential . However, a small subset of patients present with large neglected BCCs or tumours resistant to conventional treatment that have progressed to locally advanced BCC.…”
mentioning
confidence: 99%
“…The most common adverse events associated with the use of Hedgehog inhibitors include alopecia, muscle cramps and dysgeusia, among others. It has been reported that about 58–64% of patients receiving Hedgehog inhibitor treatment for aBCC develop severe hair loss (>50% of the scalp area) . Vismodegib was reported as having the highest overall incidence of all‐grade alopecia compared to the other treatments (56.9% of patients) in a recent meta‐analysis .…”
mentioning
confidence: 99%